Portal authentication HTTP redirection using netfilter NFQUEUE - Huan-jie ZHANG; Yu-liang XIA (Tongxin xuebao)
When using portal for user authentication,unauthorized user's HTTP access should be redirected to portal login page to help user do authentication.Using netfilter NFQUEUE target send unauthorized user TCP port 80 packets to user-space program redir_http.Redir_http will send IP reply packets to user do HTTP redirection with the help of raw socket.Using NFQUEUE can ensures high performance redirection,avoid troublesome development in the Linux kernel,simplify application development and improve system stability.